Use Of Injection Contraception With Changes Menstrual Cycle In Injection Kb Acceptor - Fitriani; Asri; Andi Nurfadillah Mutmainna (Jurnal Life Birth, 2019)
According to the result of the WHO study, the use of globally, the use of modern contraceptives has increased from 45%1990 to 57.4% in 2015. Several women complained about the use of a 3-moth contraceptive method causing irregular menstrual cycles, namely menstrual cycles which are shortened or elongated, bleeding spotting, and can not occur at all. The purpose of this study was to determine the relationship between injection contraceptive use and menstrual cycle changes in injectable family planning acceptors in pustu Turungan Beru Herlang District, Bulukumba District in 2018. Analytical observational research method with cross-sectional design. The population in this study was the mother who used injectable birth control, which was 233 respondents. The sample of this research is 77 people taken by using sample random sampling. The results showed that the rate of use of injectable contraceptives in the old acceptors was 61 respondents (16.0%). From the menstrual cycle results, there were 61 (61.0%) who were irregular ones were 16 (16.0%). Analysis of data using the alternative fisherman chi-square test obtained p= 0,000 means that the value of v= <a (0,05). The conclusion is that there is a relationship between the use of injectable family planning acceptors in pustu Turungan Beru herlang district in Bulukumba district in 2018. Advice to health workers to further improve the education of injectable family planning so that it is expected to mothers the mother is suitable and following her wishes.